2022
DOI: 10.1007/s11082-022-03994-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigation of the electronic and optical properties of pure and interstitial nitrogen -doped (TiO2)n cluster

Abstract: The structural and electronic properties of pure and nitrogen-doped TiO 2 nanoclusters are investigated using density functional theory (DFT) with vibrational modes. We performed numerical simulation using two methods based on theories at the Quantum Espresso/PBE and Gaussian/B3LYP/631G (d) levels. The properties of a single nitrogen-doped (TiO 2 ) n nanocluster are also computed in this study. In both cases, interstitial and substitutional Nitrogen doping at all accessible sites was examined. For the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, they investigated N-doping of Ti 9 O 18 and Ti 28 O 56 nanoclusters and found that the interstitial N formation energy is lower than that of substitutional N. Additional theoretical calculations predicted a decreasing of the band gap due to the presence of nitrogen, in agreement with results from UV–vis spectroscopy. 27 Combining the density functional theory (DFT) calculations and extended X-ray absorption fine structure (EXAFS) techniques, Ceotto et al 28 studied the nitrogen location in nanocrystalline N-doped TiO 2 and concluded that, at a low concentration of N-doping, N atoms substitute O atoms, whereas at higher N-doping concentrations, oxygen vacancies appear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they investigated N-doping of Ti 9 O 18 and Ti 28 O 56 nanoclusters and found that the interstitial N formation energy is lower than that of substitutional N. Additional theoretical calculations predicted a decreasing of the band gap due to the presence of nitrogen, in agreement with results from UV–vis spectroscopy. 27 Combining the density functional theory (DFT) calculations and extended X-ray absorption fine structure (EXAFS) techniques, Ceotto et al 28 studied the nitrogen location in nanocrystalline N-doped TiO 2 and concluded that, at a low concentration of N-doping, N atoms substitute O atoms, whereas at higher N-doping concentrations, oxygen vacancies appear.…”
Section: Introductionmentioning
confidence: 99%